Factors influencing the empowerment of women coffee growers in southern Colombia - Ana Milena Yoshioka Vargas; Jennifer Finke; María Irene Victoria Morales; Luis Eduardo Girón Cruz; Alexander Alegría Castellanos; Gustavo Adolfo Gómez Florez; Laura Mejía Posada (Cogent Social Sciences, 2023)
This study evaluated the factors influencing the empowerment of women coffee growers in Cauca Department in southern Colombia who are associated with and linked to inclusive global markets. We applied a mixed-methods approach during the research process to adapt the Three Domains of Empowerment sub-index of the Project-level Women’s Empowerment in Agriculture Index with qualitative pre-survey information from participants. After calculating the Three Domains of Empowerment sub-index, we assembled focus groups to expand the analysis and interpretation of the quantitative results. The findings showed that, despite high levels of participation in the productive component of coffee growing and their associativity, women were not completely empowered; 63.3% of participating women reported being disempowered. The three indicators contributing most to their disempowerment were social control, visiting key locations, and work balance. Likewise, through discussions with participating women, we identified sociocultural conditions such as intimate partner violence, household power structures, concerns regarding violent situations related to armed conflict, and institutional weaknesses that limit women coffee growers’ empowerment within both the private and public spheres.